The Impact of AI Knowledge, Attitudes on Technology, and Usage Experience on Student Self-Confidence (A Study at the Faculty of Business and Informatics) - Bayu Suratmoko; Masrifah Dwi Yanti; mohamad rafii rafii (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The disruption caused by Artificial Intelligence (AI) requires psychological readiness, particularly self-confidence, among students as future professionals. This study aims to analyze and empirically test the impact of AI Knowledge (X1), Attitude on Technology (X2), and Usage Experience (X3) on students' Self-Confidence (Y). Using an explanatory quantitative approach, data were collected through an online survey of 306 students (as a sample) at the Faculty of Business and Informatics, Muhammadiyah University Palangkaraya (N=842). The data were analyzed using PLS-SEM with SmartPLS 4. The model evaluation results showed that the data were valid and reliable, with strong predictive power (Q²=0.620). The bootstrapping hypothesis test results showed that all three hypotheses were accepted: AI Knowledge (T=2.697; P=0.004), Attitude on Technology (T=5.046; P=0.000), and Usage Experience (T=5.875; P=0.000) all have a positive and significant effect on Self-Confidence. These three variables collectively explain 63.3% of the variance in Self-Confidence (R²=0.633). Experience of Use (X3) proved to be the most dominant predictor (coefficient=0.425; f²=0.195), followed by Attitude (X2) (f²=0.129), and Knowledge (X1) (f²=0.027). This study concludes that to build student self-confidence, practice-based (“doing”) and affective (‘feeling’) interventions have a much greater substantive impact than cognitive (“knowing”) interventions.